Healing and Care Practices. Voices of Women Sellers of Medicinal Plants in Chetumal, Mexico (Revista Rupturas, 2026)
This text is the result of research focused on women vendors of medicinal plants in three markets and two open-air markets in the city of Chetumal, Quintana Roo, Mexico. It offers a critical reflection on care work and healing, exploring how these practices and knowledge have found visibility in diverse contemporary settings. The text is structured in four sections: a theoretical framework, materials and methods used, results, and main findings. The findings were analyzed in three axes of analysis: the relationship between care and healing and the appropriation and defense of territory; the timing and rhythms of their daily activities; and the relationships and bonds the women establish to heal and care.
Keywords: territory; time management; relationships; bonds; everyday life